Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-4 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
Caudal part of the human spinal cord from the dorsal side. Lig. dent. = denticulate ligament. Dissection of the Author.